Memória e identidade nas marés do Amazonas, de Iramel Lima: análise literária e sociológica de uma obra “inacabada” - BORGES, Emília Garçon (UNIFAP – Universidade Federal do Amapá, 2022)
The article aims to analyze the importance of the work "Nas marés do Amazonas" by Iramel Lima, to build the history and identity of Amapá people, from the inhabitants of the Archipelago Bailique, the work setting. Studies on the importance of individual and collective memories for the formation of the identity of a people guide our discussions. We evaluate the literary and historical importance of the work of Lima and point at the conclusion of the work, editing and planning failures in the construction of which is his first novel, and provide inputs to those problems. The backwaters of the Amazon is a predominantly written work in direct discourse, thereby exposing the form of research used by the author to support his creation: the oral report.